Teacher, student, and counselor beliefs about the causes and solutions of mathematics anxiety - Kho, Rex Marcus Tan; Bustos-Orosa, Maria Alicia; Reyes, Jose Alberto S. (2009)
Differences in beliefs of students, teachers, and counselors regarding the causes of and solutions to mathematics anxiety were investigated in high school using a mixed-methods design with sample sizes of 96 respondents for the qualitative phase and 75 respondents for the quantitative phase respectively. Results obtained from differences in mean ratings provided by the respondents and treatment effects of the type of respondent on the causes and solutions indicate that conceptualizations construed by students, teachers, and counselors about mathematics anxiety vary across several dimensions. Findings also indicate that mathematics anxiety experienced by students have causes and solutions that can be both dispositional and situational in nature. The findings of this study may consequently serve as reference for future research and program interventions regarding mathematics anxiety.
Keywords: Math anxiety; High school student attitudes